Saturation mutagenesis of the UASNTR (GATAA) responsible for nitrogen catabolite repression-sensitive transcriptional activation of the allantoin pathway genes in Saccharomyces cerevisiae. - Bysani, N (1991)
Saturation mutagenesis of the UASNTR element responsible for GLN3-dependent, nitrogen catabolite repression-sensitive transcriptional activation of allantoin pathway genes in yeast cells identified the dodecanucleotide sequence 5'-TTNCTGATAAGG-3' as the minimum required for UAS activity. There was significant flexibility in mutant sequences capable of supporting UAS activity, which correlates well with the high variation in UASNTR homologous sequences reported to be upstream of the DAL and DUR genes. Three of nine UASNTR-like sequences 5' of the DAL5 gene supported high-level transcriptional activation. The others, which contained nonpermissive substitutions, were not active.